Effects of extracellular ATP on local and systemic responses of bean (Phaseolus vulgaris L) leaves to wounding. Issue 3 (4th March 2019) - Wang, Qing-Wen; Jia, Lin-Yun; Shi, Dai-Long; Wang, Rong-fang; Lu, Li-Na; Xie, Jia-Jia; Sun, Kun; Feng, Han-Qing; Li, Xin
ABSTRACT: Wounding increased the extracellular Adenosine 5ʹ-triphosphate (eATP) level of kidney bean leaves. Treatment with wounding or exogenous ATP increased the hydrogen peroxide (H2 O2 ) content, activities of catalase and polyphenol oxidase, and malondialdehyde content in both the treated and systemic leaves. Pre-treatment with ATP-degrading enzyme, apyrase, to the wounded leaves reduced the wound-induced local and systemic increases in H2 O2 content, activities of catalase and polyphenol oxidase, and malondialdehyde content. Application of dimethylthiourea (DMTU) and diphenylene iodonium (DPI) to the wounded and ATP-treated leaves, respectively, reduced the wound- and ATP-induced local and systemic increases in H2 O2 content, activities of catalase and polyphenol oxidase, and malondialdehyde content. Moreover, the wound- and ATP-induced systemic increases of these physiological parameters were suppressed when DMTU or DPI applied to leaf petiole of the wounded and ATP-treated leaves. These results suggest that eATP at wounded sites could mediate the wound-induced local and systemic responses by H2 O2 -dependent signal transduction. Graphical abstract: : Wounding triggered physiological responses which were related to eATP. eATP initiates a systemic signal, which require the accumulation of H2 O2 in local and systemic tissues